Analisis Spasial Bencana Banjir Di Kota Padang Periode Tahun 2020-2024 - Harvia, Rykhe; Juita , Erna; Despica , Rika (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2024)
During the period of 2020-2024, the frequency and intensity of flooding in the City of Padang showed a significant increase, impacting the community. This study aims to: 1) identify the spatial distribution of flood disasters in the City of Padang, 2) classify the types of floods that occurred, and 3) identify the impact of floods on damage and losses. This type of research is quantitative, with the population being all sub-districts in the City of Padang. The sample was taken using total sampling, covering all sub-districts affected by flooding, totaling 11 sub-districts, including Padang Barat, Padang Utara, Padang Timur, Padang Selatan, Nanggalo, Kuranji, Lubuk Begalung, Lubuk Kilangan, Pauh, Koto Tangah, and Bungus Teluk Kabung. The data analysis technique used is spatial analysis. The results of the study show that there were 121 flood events distributed across various sub-districts, with the highest occurrences in Koto Tangah (56 events) and the fewest in Padang Barat (2 events). Floods in the City of Padang are classified into three categories: fluvial floods, tidal floods, and flash floods. Fluvial floods are the most common, while tidal floods occur in Padang Barat, and flash floods occur in Lubuk Begalung. The impact of the floods includes damage and losses; Lubuk Begalung experienced the most significant damage, with 70 houses affected, and the largest losses occurred in Pauh in 2023, amounting to Rp1,786,150,000, while the lowest losses occurred in Koto Tangah in 2022, amounting to Rp18,000,000.